The Effect of Vitamin D Supplementation on Changes in TNF-? Levels and Exciting Frequency in Epilepsy Patients - Riri Daynuri; Endang Kustiowati; Amin Husni; Retnaningsih Retnaningsih; Herlina Suryawati; Rahmi Ardhini (Diponegoro International Medical Journal, 2025)
Background: Epilepsy, a neurological disorder, is a global public health problem. The active form of vitamin-D is 5000IU/day for 42 days, able to push inflammation and change the balance between inhibitory cytokine and excitatory cytokine, to suppress recurrent seizuresObjective: Analyze the effect of vitamin-D 5000 supplementations on changes in TNF-α levels pre-and-post-vitamin-D supplementation and changes in the frequency of seizures pre-and post-vitamin-D supplementation in epilepsy patients.Methods: This research is a quasi-experimental analytic observational study with a pre-and-post-tests approach without control. Subjects were patients diagnosed with epilepsy who had met the inclusion criteria. Previous research subjects were checked for TNF-α levels, then given vitamin-D supplementation of 5000IU/day for 42 days, then rechecked TNF-α levels. Then performed a bivariate analysis.Results:  There was a significant difference between changes in TNF-α pre-and-post-levels of vitamin-D supplementation of 5000IU/day for 42 days (p<0.001). There was a significant difference in the frequency of seizures pre-and-post-levels of vitamin D supplementation 5000IU/day for 42 days (p=0.002). There is a significant relationship between (d)TNF-α on (d)the frequency of seizures pre-and-post-vitamin-D supplementation 5000IU/day, strongly and positively related (p<0.001; r=0.661). There is no relationship between risk factors with (d)TNF-α. There is no relationship between risk factors with (d)seizure frequency.Conclusion: There is a significant difference in the levels of TNF-α pre-and-post-vitamin-D supplementation. There is a significant difference between the frequency of seizures pre-and-post-vitamin-D supplementation. There is a relationship between (d)TNF-α and (d)the frequency of seizures pre-and-post-vitamin-D supplementation.